Kearifan Lokal pada Proses Pembangunan Sistem Fisik (Physical System) Rumah Tinggal Tradisional Melayu Tipe Potong Limas di Kota Pontianak, Kalimantan Barat - wahyudin ciptadi; Erwin Rizal Hamzah; Izzazaya Binta (Politeknik Negeri Pontianak, 2021)
Local genius in the process of a building physical system of traditional houses in each region is unique by its building construction. One of them is a traditional Malay house of Potong Limas in Pontianak, West Kalimantan. The traditional Malay house of Potong Limas is characterized by the use of Belian wood construction materials for the house foundation, floor, frame and roof. All parts of the house become a unitary system, which is interrelated and related. The purpose of this research is to identify the physical system of the building which includes the structural aspects of the upper element (head), middle element (body), and lower element (leg) in the construction process, and to produce building drawing (blue print) of the traditional Malay house of Potong Limas. This study uses a rationalistic-qualitative approach by taking several research samples from the population of traditional Malay houses, Potong Limas, in Pontianak, which still exist today. This research uses several stages of the implementation process: 1) data collection stage, 2) data analysis stage, 3) discussion of research results. The results of this study are documented science and technology-social and cultural products in the form of building drawing (blue print) of the physical system development process which was formed in a traditional Malay House type Potong Limas in Pontianak.